The role of ABCB1 and ABCA1 in beta-amyloid clearance at the neurovascular unit in Alzheimer's disease - ElAli, Ayman; Rivest, Serge (Frontiers in Physiology, 2013)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects elderly persons, evolving with age to reach severe cognitive impairment. Amyloid deposits and neurofibrillary tangles constitute the main pathological hallmarks of AD. Amyloid deposits are initiated by the excessive production and accumulation of beta-amyloid (Aβ) peptides in the brain. The dysfunction of the Neurovascular Unit (NVU) has been proposed to be causative in AD development, due to an impaired clearance of Aβ from the brain. Cells forming the NVU express several Adenosine Triphosphate ATP-Binding Cassette (ABC) transporters, among which ABCB1 and ABCA1 play an important role in Aβ processing. The drug transporter ABCB1 directly transports Aβ from the brain into the blood circulation, whereas the cholesterol transporter ABCA1 neutralizes Aβ aggregation capacity in an Apolipoprotein E (ApoE)-dependent manner, facilitating Aβ subsequent elimination from the brain. In the present minireview, we will summarize the contribution of ABCB1, and ABCA1 at the NVU in Aβ clearance. Moreover, we will outline and discuss the possible collaboration of ABCB1, and ABCA1 at the NVU in mediating an efficient clearance of Aβ from the brain.